2021
DOI: 10.1021/jacs.1c05017
|View full text |Cite
|
Sign up to set email alerts
|

Cellulonodin-2 and Lihuanodin: Lasso Peptides with an Aspartimide Post-Translational Modification

Abstract: Lasso peptides are a family of ribosomally synthesized and post-translationally modified peptides (RiPPs) defined by their threaded structure. Besides the class-defining isopeptide bond, other post-translational modifications (PTMs) that further tailor lasso peptides have been previously reported. Using genome mining tools, we identified a subset of lasso peptide biosynthetic gene clusters (BGCs) that are colocalized with genes encoding protein l-isoaspartyl methyltransferase (PIMT) homologues. PIMTs have an i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(81 citation statements)
references
References 63 publications
(105 reference statements)
2
66
0
Order By: Relevance
“…Members of this family are related to IPR000682, which converts l -isoaspartyl and d -aspartyl residues to l -Asp, and IPR027573, which frequently co-occurs with lanthipeptide biosynthetic enzymes . Recently, members of the latter family, OlvS A , TceM, and LihM, were implicated in RiPP biosynthesis , OlvS A catalyzes a three-step reaction (methylation, cyclization, and hydrolysis) of a highly conserved l -Asp to the corresponding l -isoaspartyl residue in OlvA, the cognate lanthipeptide precursor peptide. TceM and LihM introduce stable aspartimide moieties in the lasso peptides, cellulonodin-2 and lihuanodin, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Members of this family are related to IPR000682, which converts l -isoaspartyl and d -aspartyl residues to l -Asp, and IPR027573, which frequently co-occurs with lanthipeptide biosynthetic enzymes . Recently, members of the latter family, OlvS A , TceM, and LihM, were implicated in RiPP biosynthesis , OlvS A catalyzes a three-step reaction (methylation, cyclization, and hydrolysis) of a highly conserved l -Asp to the corresponding l -isoaspartyl residue in OlvA, the cognate lanthipeptide precursor peptide. TceM and LihM introduce stable aspartimide moieties in the lasso peptides, cellulonodin-2 and lihuanodin, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…44,55 Those found in lasso peptides are especially numerous, including glycosylation, phosphorylation, acetylation, C-terminal methylation, β-hydroxylation, deimination, epimerization to d -amino acids, 44 or aspartimide formation from l -aspartate residues, as recently described. 56 Other RiPP classes have also been described as being further modified, such as thiopeptides, and especially lanthipeptides that can accept hydroxylation, epimerization at α-carbons or halogenation, 55 or can acquire β-amino acids with the formation of isoaspartate (iso-Asp) residues. 43 Such additional tailoring PTMs occur due to the dedicated post-tailoring enzymes (see Section 3.1.3).…”
Section: Ribosomally Synthesized Peptides In Their Producersmentioning
confidence: 99%
“…They both introduce an aspartimide ring into the macrolactame ring of the lasso peptides. 56 While the conventional role of canonical PIMTs is to reverse iso-Asp residues (the β-amino acids resulting from protein aging) to l -Asp, with aspartimide ( i.e. succinimide) as an intermediate, the lasso peptide O -methyltransferases act directly on Asp residues that are methylated and lead to aspartimide as the final products, and not a reaction intermediate.…”
Section: Ribosomally Synthesized Peptides In Their Producersmentioning
confidence: 99%
“…Protein L-isoaspartyl methyltransferases (PIMTs) usually have a crucial role in protein repair, recognizing and repairing abnormal isoaspartate (isoAsp) residues to L-Asp through a SAM-dependent methyl esterification reaction [58]. In total, 48 lasso peptide BGCs were uncovered bearing genes annotated as O-methyltransferases that belong to PIMT homologues, and the extremely conserved Asp6 in all the putative precursor peptides suggested that it might be the modification site [59]. Heterologous expression of two clusters from actinobacterium Thermobifida cellulosilytica (tce) and firmicute Lihuaxuella thermophila (lih) (Figure 9a) resulted in the discovery of cellulonodin-2 and lihuanodin, featuring an unconventional succinimide moiety (also known as aspartimide) in the macrolactam ring.…”
Section: Succinimidationmentioning
confidence: 99%
“…Notably, TceM and LihM carried out dehydration on Asp instead of isoAsp, which is in stark contrast to canonical PIMTs. In addition, both TceM and LihM only recognized the threaded lasso peptides rather than linear precursors or isopeptide-bonded rings (Figure 9b) [59].…”
Section: Succinimidationmentioning
confidence: 99%